Mawlawi Rumi’s Philosophical Anthropology with an Emphasis upon the Perfect Man - Miri, Seyyed Mohsen (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2012)
There are a variety of ways for linking the Orient with the Occident the most enduring and influential of them being anthropology. Mawlawi Rumi is among the most outstanding figures whose profound and brilliant thoughts can open new horizons to the contemporary Eastern and Western worlds. The present essay surveys and expounds on some of his anthropological views, especially on the perfect man.